The Limits of Communication - Quarry Wendy; Ramírez Ricardo (Nordicom Review, 2012)
When asked by a Mozambican firm to assist in the development of a communication strategy for the country’s Land Law, we had doubts. We had read about the issue of ‘land grabbing’ in Africa and feared we might become part of that problem. We knew that any communication strategy devoted solely to outreach and public relations would not reach the illiterate farmer. But when the client agreed that the strategy would include a component focused on communicating with and from the small rural landowner, we accepted the contract. We worked well with the local team and delivered the product on time. However, a year later we learned that the component allowing for feedback from rural farmers had been cut, and that the strategy was yet to be implemented. What went wrong? And will the communication strategy do some good, or will it contribute to people giving up land under false promises?